MASALAH HUBUNGAN SOSIAL PESERTA DIDIK KELAS TINGGI DAN PERAN GURU KELAS DALAM MENGATASINYA DI SD N 11 2X11 KAYUTANAM KABUPATEN PADANG PARIAMAN - Deni, Sri Rahma (Bimbingan dan Konseling, 2014)
School age Child of Base Their Primary School present more compared to matured behaviour of agechild early. This research aim to to ( 1) to explaining the problem of social relation of educative by participantin Elementary School ( 2) Explaining role of class teacher in overcoming problems of social relation ofeducative participant. Research have the character of quantitative descriptive for deskrip of is problem of socialrelation of educative by participant of high class and role of class teacher in overcoming him SD N 11 WoodPlant Sub-Province Field Pariah. Population in this research [is] entire/all educative by participant of class ofIV and of V in SD N 11 Wood Plant Sub-Province Field Pariah and of sampel research taken by using techniqueof purposive sampling amounting to 62 people. Collecting use enquette, result of research is problem of socialrelation of related/relevant educative participant problems of adjustment with friend coeval pertained to haveproblem and role of class teacher in social educative participant related to aspect maintain behavior ofappropriate student can be categorized that role of teacher have is good enough.